Grounding lists: building common ground as a multimodal practice in interaction - Dankel, Philipp; Titze, Simon; Schröder, Ulrike (Interactional linguistics, 2024)
Abstract: Drawing on findings from three distinct corpora encompassing interactions in Spanish, Portuguese, and German, this study investigates the role of lists as strategic devices employed by interlocutors in everyday storytellings and positioning activities to establish common ground (CG). Termed ‘grounding lists’, our research identifies them as a distinct communicative practice for dynamically co-building CG. We found three domains to be most relevant in our data: (a) Personal CG emerging from biographically shared experiences, (b) Communal CG emerging from shared cultural knowledge, and (c) Communal CG emerging from shared everyday knowledge. Our findings reveal the primary characteristics of grounding lists being stylized prosody, reduced itemization, general extenders, lexical elements or quotatives in the onset projecting generalizability, early affiliation, reported speech, as well as gestural depiction. Through empirical analysis, we demonstrate the extent to which each type of CG aligns with these identified features of grounding lists and highlight that it is particularly the dominant use of the list as an abstract gestalt, less as a sedimented practice in itself, that defines grounding lists. This kind of list is strongly marked by its gestalt projection, enabling intersubjectivity and co-building of CG through animated speech and gestural enactment.